2021
DOI: 10.3390/polym13050765
|View full text |Cite
|
Sign up to set email alerts
|

Durability of Externally Bonded Fiber-Reinforced Polymer Composites in Concrete Structures: A Critical Review

Abstract: Externally bonded fiber-reinforced polymer composites have been in use in civil infrastructure for decades, but their long-term performance is still difficult to predict due to many knowledge gaps in the understanding of degradation mechanisms. This paper summarizes critical durability issues associated with the application of fiber-reinforced polymer (FRP) composites for rehabilitation of concrete structures. A variety of factors that affect the longevity of FRP composites are discussed: installation, quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 113 publications
0
23
0
Order By: Relevance
“…Thermosetting polymers (such as epoxy, acrylic, vinyl ester resins) are frequently used as adhesives, coatings, matrices for composites: since in all the mentioned applications the materials are outdoor exposed and subject to more or less severe weathering, the possibility to obtain reliable predictions of their long-term performance with accelerated aging procedures represents an asset [ 45 , 46 , 47 , 48 ]. Durability studies appeared in literature on the effects caused on thermosetting matrices for composites by artificial and natural weathering have shown that even in the case of this class of materials it is not possible to obtain an adequate correlation of the test results from natural exposure and accelerated aging procedures.…”
Section: Comparison Between On Field Durability Tests With Accelerated Proceduresmentioning
confidence: 99%
“…Thermosetting polymers (such as epoxy, acrylic, vinyl ester resins) are frequently used as adhesives, coatings, matrices for composites: since in all the mentioned applications the materials are outdoor exposed and subject to more or less severe weathering, the possibility to obtain reliable predictions of their long-term performance with accelerated aging procedures represents an asset [ 45 , 46 , 47 , 48 ]. Durability studies appeared in literature on the effects caused on thermosetting matrices for composites by artificial and natural weathering have shown that even in the case of this class of materials it is not possible to obtain an adequate correlation of the test results from natural exposure and accelerated aging procedures.…”
Section: Comparison Between On Field Durability Tests With Accelerated Proceduresmentioning
confidence: 99%
“…[15][16][17] Polymers have been widely used in both consumer products and engineering applications such as aviation, automobiles, ships, infrastructure, military supplies, and many other fields. [18][19][20][21][22][23][24][25] Over the past few decades, polymer materials kept developing primarily in the experimental way. Some cutting-edge techniques, such as click polymerizations, chain-shuttling reactions, and controlled living radical polymerizations, have been successfully put into use for the design of new polymers meeting the market requirements.…”
Section: Introductionmentioning
confidence: 99%
“…For more than 30 years, engineers have used externally bonded fiber-reinforced polymers to strengthen and increase the load-carrying capacity of reinforced concrete structures, but due to limited test data and a lack of comprehensive design standards, the engineering community at large is not very familiar with the design and application of fiber-reinforced polymers (FRP) to strengthen existing infrastructures. Hence, more test data are required to study failure modes [ 11 ]. Guo et al used three kinds of fibers, including glass fibers, basalt fibers, and steel fibers, to investigate their influences on the racking resistance of asphalt mixtures and adopted the digital image correlation (DIC) technique to measure the full-field strain and deformation.…”
Section: Introductionmentioning
confidence: 99%